Analisis Aktivitas Belajar Siswa Melalui Penerapan Model Pembelajaran Discovery Learning di SMAN 06 Kota Bengkulu - Zufiyardi, Zufiyardi; Ayuni, Rossa; Resti, Resti (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This study aims to provide a clear understanding of student’ learning activities thorough the implementation of the Discovery Learning model at SMAN 06 Bengkulu city. This research employs a descriptive analysis approach, focusing on student’ learning activities in economics lessons using the Discovery Learning model. The research subjects consisted of an economics teacher and 37 students from class X.D. the date were collected through observation, interviews, and documentation.the findings indecate that the implementation of the Discovery Learning model by the economics teacher wa carride out effectively and in accprdance with the model’s procedurl steps. The use of thid model has proven to enhance students’ learning activity and independence. Besed on the activity indicators, improvenments, engagement in independent tasks, probelem-solving activities, emotional involvement and motivation, and time management.